2013
DOI: 10.1186/1746-4269-9-24
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants, traditional medicine, markets and management in far-west Nepal

Abstract: BackgroundModern therapeutic medicine is historically based on indigenous therapies and ethnopharmacological uses, which have become recognized tools in the search for new sources of pharmaceuticals. Globalization of herbal medicine along with uncontrolled exploitative practices and lack of concerted conservation efforts, have pushed many of Nepal's medicinal plants to the verge of extinction. Sustainable utilization and management of medicinal plants, based on traditional knowledge, is therefore necessary.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(105 citation statements)
references
References 45 publications
7
91
0
Order By: Relevance
“…Most of the herbal preparation is given orally to cure human ailments except skin diseases. Similar observations were reported in various ethnic communities in Nepal, adjoining counties and abroad (Bhattarai et al, 2005;Upreti et al, 2010;Singh et al, 2012;Kunwar et al, 2013;Lulekal et al, 2013;Luitel et al, 2014).…”
Section: Forms Of Medication Usedsupporting
confidence: 86%
“…Most of the herbal preparation is given orally to cure human ailments except skin diseases. Similar observations were reported in various ethnic communities in Nepal, adjoining counties and abroad (Bhattarai et al, 2005;Upreti et al, 2010;Singh et al, 2012;Kunwar et al, 2013;Lulekal et al, 2013;Luitel et al, 2014).…”
Section: Forms Of Medication Usedsupporting
confidence: 86%
“…Previous studies in this area [5,62,63] were used as a database to retrieve the biogeographical distribution of species in the region. Species origin, usefulness, use value index, growth form, parts used, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Kunwar et al (2006) while carrying out ethnomedicinal survey in Nepal Himalayas found that the most frequently utilized plant part was the root/rhizome/tuber (26.15%), followed by leaf (23.84%) and flower and fruit (21.53%). Similarly, Kunwar et al (2013) found that the most frequently utilized plant parts were roots and rhizomes of 38 species, followed by fruits of 26 species, leaves of 22 species etc. Similar results were obtained by (Kunwar et al, 2010) from Nepal.…”
Section: Discussionmentioning
confidence: 96%